Placental Alpha Microglobulin-1 Compared With Fetal Fibronectin to Predict Preterm Delivery in Symptomatic Women. Issue 6 (December 2017) - Wing, Deborah A.; Haeri, Sina; Silber, Angela C.; Roth, Cheryl K.; Weiner, Carl P.; Echebiri, Nelson C.; Franco, Albert; Pappas, Lanissa M.; Yeast, John D.; Brebnor, Angelle A.; Quirk, J. Gerald; Murphy, Aisling M.; et al.
Abstract : OBJECTIVE: To compare the rapid bedside test for placental α microglobulin-1 with the instrumented fetal fibronectin test for prediction of imminent spontaneous preterm delivery among women with symptoms of preterm labor. METHODS: We conducted a prospective observational study on pregnant women with signs or symptoms suggestive of preterm labor between 24 and 35 weeks of gestation with intact membranes and cervical dilatation less than 3 cm. Participants were prospectively enrolled at 15 U.S. academic and community centers. Placental α microglobulin-1 samples did not require a speculum examination. Health care providers were blinded to placental α microglobulin-1 results. Fetal fibronectin samples were collected through speculum examination per manufacturer requirements and sent to a certified laboratory for testing using a cutoff of 50 ng/mL. The coprimary endpoints were positive predictive value (PPV) superiority and negative predictive value (NPV) noninferiority of placental α microglobulin-1 compared with fetal fibronectin for the prediction of spontaneous preterm birth within 7 days and within 14 days. RESULTS: Of 796 women included in the study cohort, 711 (89.3%) had both placental α microglobulin-1 and fetal fibronectin results and valid delivery outcomes available for analysis. The overall rate of preterm birth was 2.4% (17/711) within 7 days of testing and 4.2% (30/711) within 14 days of testing with respective rates of spontaneous preterm birth of 1.3% (9/703) and 2.9% (20/701). Fetal fibronectin was detected in 15.5% (110/711), and placental α microglobulin-1 was detected in 2.4% (17/711). The PPVs for spontaneous preterm delivery within 7 days or less among singleton gestations (n=13) for placental α microglobulin-1 and fetal fibronectin were 23.1% (3/13) and 4.3% (4/94), respectively ( P <.025 for superiority). The NPVs were 99.5% (619/622) and 99.6% (539/541) for placental α microglobulin-1 and fetal fibronectin, respectively ( P <.001 for noninferiority). CONCLUSION: Although placental α microglobulin-1 performed the same as fetal fibronectin in ruling out spontaneous preterm delivery among symptomatic women, it demonstrated statistical superiority in predicting it. Abstract : Placental α microglobulin-1 more accurately predicts spontaneous preterm delivery within 7 and 14 days of testing among symptomatic women than fetal fibronectin.